GENETIC PREDICTORS OF ATRIAL FIBRILLATION - A. V. Kuskaeva; S. Yu. Nikulina; A. A. Chernova; N. V. Aksyutina (Рациональная фармакотерапия в кардиологии)
Atrial fibrillation (AF) is the most common heart rhythm disturbance. It is believed that the primary form of AF is genetically determined in most cases, but the genetic component cannot be excluded in the secondary form of AF. AF is a heterogeneous disease and many authors proved its relationship with other genetic heart disease. In most cases, certain combinations of polymorphisms of different genes promote the development of AF. The study of genes of renin-angiotensin-aldosterone system (RAAS) is especially important, because the role of this system in AF pathogenesis is currently studding most intensively. These studies are of great practical interest, as associative effect of angiotensin-converting enzyme inhibitors and angiotensin II receptor antagonists in the prevention of AF is revealed. RAAS blockers are able not only to reduce the risk of new-onset AF in hypertensive and normotensive patients but also prevent recurrence of AF. Furthermore, experimental studies showed that RAAS blockers prevent not only the remodeling of the left ventricle, and also the left atrium, pointing to the pathogenesis of AF. So, screening for susceptibility genes and the study of their polymorphism is currently an important focus in the study of AF.